Construction of integrated gene logic-chip. Issue 10 (October 2018) - Masubuchi, Takeya; Endo, Masayuki; Iizuka, Ryo; Iguchi, Ayaka; Yoon, Dong; Sekiguchi, Tetsushi; Qi, Hao; Iinuma, Ryosuke; Miyazono, Yuya; Shoji, Shuichi; Funatsu, Takashi; Sugiyama, Hiroshi; et al.
Abstract In synthetic biology, the control of gene expression requires a multistep processing of biological signals. The key steps are sensing the environment, computing information and outputting products1 . To achieve such functions, the laborious, combinational networking of enzymes and substrate-genes is required, and to resolve problems, sophisticated design automation tools have been introduced2 . However, the complexity of genetic circuits remains low because it is difficult to completely avoid crosstalk between the circuits. Here, we have made an orthogonal self-contained device by integrating an actuator and sensors onto a DNA origami-based nanochip that contains an enzyme, T7 RNA polymerase (RNAP) and multiple target-gene substrates. This gene nanochip orthogonally transcribes its own genes, and the nano-layout ability of DNA origami allows us to rationally design gene expression levels by controlling the intermolecular distances between the enzyme and the target genes. We further integrated reprogrammable logic gates so that the nanochip responds to water-in-oil droplets and computes their small RNA (miRNA) profiles, which demonstrates that the nanochip can function as a gene logic-chip. Our approach to component integration on a nanochip may provide a basis for large-scale, integrated genetic circuits. DNA origami-based integrated gene transcription modules enable the rational design of transcription activity. Architectural modalities between gene and RNA polymerase allow the autonomous response to various signals with reprogrammable logic gates.